2022
DOI: 10.3389/fmolb.2022.860323
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Apparent Imbalanced Epi-lncRNAs Prognostic Model Based on Multi-Omics Data in Pancreatic Cancer

Abstract: Background: Globally, pancreatic adenocarcinoma is a recognized cause of pancreatic death (PAAD) associated with high mortality. Long non-coding RNAs (lncRNAs) play an important role in several biological processes in pancreatic cancer.Methods: The gene expression profile of PAAD patients were obtained from The Cancer Genome Atlas (TCGA) database. The limma package was used to identify epigenetic disorders of lncRNAs and PCG. Subsequently, the genomic characteristics and landscape of lncRNAs were explored. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In PC, LINC00941 expression was found to be higher in pancreatic cancer tissues, and its localization was primarily observed in the cytosol of tumor cells. LINC00941 expression positively correlated with advanced pathological features [36,40,42], and higher expression levels of LINC00941 were associated with unfavorable prognoses in PC patients [36,37,40,42,43,48,49], further highlighting its significance as a prognostic biomarker for PC. Overall, the consistent upregulation of LINC00941 in various gastrointestinal cancers and its association with clinical features and patient outcomes shows its potential as a valuable biomarker for diagnosis, prognosis and risk assessment of these diseases.…”
Section: Studies With Clinical Patient Samplesmentioning
confidence: 87%
See 2 more Smart Citations
“…In PC, LINC00941 expression was found to be higher in pancreatic cancer tissues, and its localization was primarily observed in the cytosol of tumor cells. LINC00941 expression positively correlated with advanced pathological features [36,40,42], and higher expression levels of LINC00941 were associated with unfavorable prognoses in PC patients [36,37,40,42,43,48,49], further highlighting its significance as a prognostic biomarker for PC. Overall, the consistent upregulation of LINC00941 in various gastrointestinal cancers and its association with clinical features and patient outcomes shows its potential as a valuable biomarker for diagnosis, prognosis and risk assessment of these diseases.…”
Section: Studies With Clinical Patient Samplesmentioning
confidence: 87%
“…LINC00941 has been studied in various GI cancer types, including squamous cell carcinoma (ESCC) [35,39], gastric cancer (GC) [45,46], colorectal cancer (CRC) [41,44], hepatocellular carcinoma (HCC) [47], and pancreatic cancer (PC) [36,37,40,42,43,48,49]. Research have shown that LINC00941 plays a regulatory role in GI development by influencing key molecules and genes involved in a series of biological processes, such as proliferation, invasion, migration, and EMT (Figure 1).…”
Section: Linc00941 In Gastrointestinal Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which LINC00663 regulates tumorigenesis remain unclear. Although LINC00663 can suppress the expression of oncogene ENO1 in breast cancer 37 , it was upregulated in pancreatic cancer and glioma cells, promoting tumor progression 38 , 39 . The roles of ITGA9-AS1 and the interactions among the four lncRNAs have been relatively less studied.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis and ferroptosis are newly discovered programmed cell deaths recently [ 47 ]. AL161431.1 acts as an autophagy- and prognosis-relevant lncRNA in NSCLC [ 48 ], with epigenetically aberrant regulation in LUAD [ 49 ] and pancreatic adenocarcinoma [ 50 ]. In addition, AL161431.1 is linked to hypoxia status and immune microenvironment of LUAD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%